2011
DOI: 10.1016/s0140-6736(11)61040-4
|View full text |Cite
|
Sign up to set email alerts
|

Intensified chemotherapy with ACVBP plus rituximab versus standard CHOP plus rituximab for the treatment of diffuse large B-cell lymphoma (LNH03-2B): an open-label randomised phase 3 trial

Abstract: SummaryBackground The outcome of diff use large B-cell lymphoma has been substantially improved by the addition of the anti-CD20 monoclonal antibody rituximab to chemotherapy regimens. We aimed to assess, in patients aged 18-59 years, the potential survival benefi t provided by a dose-intensive immunochemotherapy regimen plus rituximab compared with standard treatment plus rituximab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
173
1
12

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 318 publications
(195 citation statements)
references
References 27 publications
9
173
1
12
Order By: Relevance
“…13 First-line high-dose chemotherapy plus rituximab followed by autologous stem-cell transplant has also not improved outcomes compared with rituximab-chemotherapy alone. 23,24 By contrast, in a study by the GELA group, 25 a signifi cant survival advantage was reported with R-ACVBP compared with R-CHOP-21 in 380 young patients with low-risk or low-intermediate-risk disease. After a median follow-up of 44 months, the 3-year eventfree survival was 81% in the R-ACVBP group compared with 67% with R-CHOP-21, and 3-year PFS was 87% and 73%, respectively.…”
Section: Discussionmentioning
confidence: 89%
“…13 First-line high-dose chemotherapy plus rituximab followed by autologous stem-cell transplant has also not improved outcomes compared with rituximab-chemotherapy alone. 23,24 By contrast, in a study by the GELA group, 25 a signifi cant survival advantage was reported with R-ACVBP compared with R-CHOP-21 in 380 young patients with low-risk or low-intermediate-risk disease. After a median follow-up of 44 months, the 3-year eventfree survival was 81% in the R-ACVBP group compared with 67% with R-CHOP-21, and 3-year PFS was 87% and 73%, respectively.…”
Section: Discussionmentioning
confidence: 89%
“…74 Improved outcomes and lower CNS relapse rates have been reported in young patients for R-ACVBP vs. R-CHOP associated with IT MTX in both arms, but high dose systemic MTX being administered only in the R-ACVBP arm. 75 Other IT drugs: A number of other drugs including liposomal cytarabine (LC) and rituximab can be administered intrathecally.…”
Section: 4mentioning
confidence: 99%
“…Lymphoma management was classified as: "chemotherapy1/-rituximab", "antiviral treatment alone (AT)", "antiviral treatment and rituximab combination (AT-R)" and "others". All 45 DLBCL patients received front-line immuno-chemotherapy with a standard anthracycline regimen (R-CHOP), except for three of them who received a dose intense anthracycline regimen (R-ACVBP) [25]. Three patients also received intensive chemotherapy with BEAM regimen (BCNU, etoposide, cytosine arabinoside and melphalan) followed by autologous bone marrow transplantation.…”
Section: Study Design and Participants Between November 2006 And Novmentioning
confidence: 99%